EFEKTIVITAS PENGGUNAAN MODEL EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR SISWA MAN 1 PONTIANAK - Kadariah, Ani; Noor, Agus Sastrawan; Chalimi, Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research for knowing by the application of learning models in the teaching and learning process, besides that conventional learning with the lecture method makes students less interested until the motivation of students to follow the teaching and learning process is reduced. This study aims to determine the effective or not use of Examples Non Examples learning models on student learning outcomes in historical subjects in MAN 1 Pontianak. The research method used an experimental method with pre-experimental design and the research design used One-Group Pretest-Postest Design. The subject of the research was the X IPS 3 MAN 1 Pontianak class. The process of determining the class that is the subject of research is based on the lowest student learning outcomes. The data collection tool used consist of interview guides, observation sheets, documents and learning outcomes tests. Based on the data analysis used using the t-test the results obtained by the significance value (Sig.2-tailed) were 0,000. Hypothesis testing Ho is rejected and Ha is accepted because 0,000 <0,05 so there are differences in learning outcomes after using Examples Non Examples learning models and the effect size of student learning outcomes is 1,29 categorized as high class. Thisresult Â that the use of Examples Non Examples learning models is effectively for teaching and learning in historical subjects in MAN 1 Pontianak. Â Keywords:Effective, Learning Outcomes, Learning Models Examples Non Examples, Historical Subjects.